1984 Annual Meetings of the Board of Governors : Summary proceedings - International Bank for Reconstruction and Development; International Finance Corporation (Washington DC The World Bank, 1984)
The summary proceedings record in alphabetical order of member countries, the texts of statements by Governors relating to the activities of the Bank, IFC and IDA.
Includes references
osc 14/7/16
Loans
Keywords: International Bank for Reconstruction and Development; Summary proceedings